The social role of food and new producer–consumer relations The case of Sundom, Vaasa, Finland - Ehrström, Peter (Socio.hu Társadalomtudományi Szemle, 2016)
This paper will discuss the social role of food and new producer–consumer relations influenced by socioeconomic and demographic transformation in an urban rurality. These topics will be addressed and enlightened through a case study, Sundom, a small urban rurality and district of Vaasa, on the west coast of Finland. Interviews highlight that transformation may influence the creation of new producer–consumer relations, but these may also be regional rather than local. New demands and tastes in food are influenced by an inflow of well–off, well–educated, new consumers. It is argued that conscious new preferences of demands and tastes may, for example, result in local consumer food circles. It is also suggested that it is not solely concerns for the quality of food that initiates the circles, but also aims to strengthen and create new social bonds in the neighborhood. Key words: transformation, food, social role, producer–consumer relations